Effect of Resveratrol Content in Red Wine on Circulating Sex Hormone‐Binding Globulin: Lessons from a Pilot Clinical Trial. Issue 16 (1st July 2022) - Briansó‐Llort, Laura; Simó‐Servat, Olga; Ramos‐Perez, Lorena; Torres‐Torronteras, Javier; Hernandez, Cristina; Simó, Rafael; Selva, David M.
Abstract : Scope: Low sex hormone‐binding globulin (SHBG) levels are associated with higher risk of developing cardiovascular disease. Epidemiological studies have shown that red wine has beneficial effects on cardiovascular disease. In this work if resveratrol content in red wine increases SHBG levels is explored. Methods and results: A pilot study aims at testing the effect of drinking for 14 days two types of red wine with different resveratrol content is conducted in 26 healthy volunteers. SHBG levels and several biochemical parameters are measured at the beginning and the end of every period. Results show that consumption of both wines does not change body mass index or biochemical markers of liver injury. The low resveratrol wine does not modify the lipid profile or SHBG levels. By contrast, red wine with high resveratrol content significantly reduces total cholesterol in both men and women. Finally, red wine with high resveratrol content increases circulating SHBG in women but not in men. Conclusions: Red wine rich in resveratrol reduces total cholesterol in men and women and increases SHBG only in women. Further research aims at investigating the potential SHBG role enhancement mediated by resveratrol regarding cardiovascular protection that presents women in comparison with men seems warranted. Abstract : Low sex hormone‐binding globulin levels increase the risk of developing cardiovascular disease (CVD). Epidemiologically, red wine has benefits on CVD. A pilot study with volunteers to test the effect of drinking two red wines with different resveratrol content is performed. Red wine rich in resveratrol lowers total cholesterol in both men and women, but only increases SHBG in women.